Infrastructures of Care for Public Housing Residents During COVID-19 Detention: Failures, Glitches and Possibilities to Care With. Issue 1 (2nd January 2023) - Olivier, Jéan-Louise; Mee, Kathleen; Power, Emma
ABSTRACT: The COVID-19 pandemic has exacerbated challenges to infrastructures of care. This study explores failures in governance, material and communication infrastructures for public housing residents during a detention order in response to a COVID-19 outbreak in Melbourne, Australia. We illustrate these failures through analysis of selected publicly available sources. Failures presented glitches in the capacity for community infrastructures of care to continue to function and emerge during the detention. Findings highlight that future pandemic planning and public housing policy needs to attentively listen to affected communities and engage with trusted community infrastructures of care, providing care that sustains our future cities.